2014
DOI: 10.5811/westjem.2014.3.19426
|View full text |Cite
|
Sign up to set email alerts
|

Improving Community Understanding of Medical Research: Audience Response Technology for Community Consultation for Exception to Informed Consent

Abstract: IntroductionThe Department of Health and Human Services and Food and Drug Administration described guidelines for exception from informed consent (EFIC) research. These guidelines require community consultation (CC) events, which allow members of the community to understand the study, provide feedback and give advice. A real-time gauge of audience understanding would allow the speaker to modify the discussion. The objective of the study is to describe the use of audience response survey (ARS) technology in EFI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…were frequently not targeted to lay people and involved on average fewer than 15 participants . Two‐way communication, when implemented, results in effective information delivery and community understanding of the EFIC research …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…were frequently not targeted to lay people and involved on average fewer than 15 participants . Two‐way communication, when implemented, results in effective information delivery and community understanding of the EFIC research …”
Section: Discussionmentioning
confidence: 99%
“…One of the most recent, largest, and best‐described efforts at community consultation was the RAMPART study . The researchers' exhaustive efforts to meet with members of the community and collect opinion data regarding willingness to participate were disappointing given the effort and expense.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Audience response systems (ARS) are an innovative way to involve community members in presentations by posing questions to audience members during the presentation. Various ARS have been used to obtain data in community-based participatory research initiatives and have been well received by AN/AI people (Gamito, Burhansstipanov, Krebs, Bemis, & Bradley, 2005; Subrahmanian et al, 2011) and other diverse community groups (Boscardin & Penuel, 2012; Cain & Robinson, 2008; Davis et al, 2012; Rodriguez, Torres, & Erwin, 2013; Vohra et al, 2014). The ARS is a computer-assisted tool that includes handheld keypads linked wirelessly to a computer system and an audiovisual display (Cain & Robinson, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…After an extensive literature search using CINAHL, Google Scholar, PubMed, MEDLINE, and PsycINFO, few research manuscripts were identified that describe the use of ARS as a data collection method in research. The research studies that did incorporate ARS used it most often as an assessment tool to analyze research participants comprehension of the consent process or to simply collect demographic data and were conducted by academic researchers (Gamito, Burhansstipanov, Krebs, Bemis, & Bradley, 2005;Keifer, Reyes, Liebman, & Juarez-Carrillo, 2014;Vohra et al, 2014). Gray et al (2016) did use ARS as a means to test the validity and reliability of the Food, Health, and Choices Questionnaire (FHC-Q) administered with ARS technology.…”
Section: Objectivementioning
confidence: 99%